2007
DOI: 10.1159/000107735
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Snoring, Maternal Obesity and Neck Circumference as Risk Factors for Pregnancy-Induced Hypertension and Preeclampsia

Abstract: Background: Physical and hormonal changes during pregnancy alter breathing patterns of pregnant women. It is possible that occult disordered breathing during sleep may be a risk factor for the development of pregnancy-induced hypertension (PIH) and preeclampsia. Objective: Our aim was to determine the incidence of self-reported snoring in pregnant women, and to investigate the relationship of snoring, obesity and neck circumference to PIH and preeclampsia. Methods: 469 pregnant women and 208 age-matched nonpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 52 publications
2
57
0
4
Order By: Relevance
“…1 SDB, independent of maternal BMI, is associated with an increased risk of hypertension in pregnancy, as well as maternal morbidity. 73,78,[80][81][82][83][84][85][86] In one study, preeclampsia, a hypertensive syndrome in pregnancy, was significantly more common among snorers than non-snorers (10% versus 4%, p < 0.05), as was gestational hypertension (14% versus 6%, p < 0.01). 87 This was recently corroborated in a report by O'Brien and colleagues, who found that pregnancy-onset snoring was independently associated with gestational hypertension (OR 2.36 [1.48-3.77], p < 0.001) and preeclampsia (OR 1.59 [1.06-2.37], p = 0.024) in 1,719 third-trimester pregnant women.…”
Section: Sleep Related Breathing Disorders In Pregnancymentioning
confidence: 99%
“…1 SDB, independent of maternal BMI, is associated with an increased risk of hypertension in pregnancy, as well as maternal morbidity. 73,78,[80][81][82][83][84][85][86] In one study, preeclampsia, a hypertensive syndrome in pregnancy, was significantly more common among snorers than non-snorers (10% versus 4%, p < 0.05), as was gestational hypertension (14% versus 6%, p < 0.01). 87 This was recently corroborated in a report by O'Brien and colleagues, who found that pregnancy-onset snoring was independently associated with gestational hypertension (OR 2.36 [1.48-3.77], p < 0.001) and preeclampsia (OR 1.59 [1.06-2.37], p = 0.024) in 1,719 third-trimester pregnant women.…”
Section: Sleep Related Breathing Disorders In Pregnancymentioning
confidence: 99%
“…Although studies have reported that snoring occurs in 14-45% of pregnant females [13][14][15], the incidence of SDB remains unknown. A few studies suggest a significant association between habitual snoring and gestational hypertensive disorders [16]. Others have assessed a potential association with neonatal outcomes [14,17], with some showing growth restriction in snorers compared with non-snorers [14] and others failing to show a correlation [17].…”
mentioning
confidence: 99%
“…Snoring in pregnancy has been associated with key adverse pregnancy outcomes such as gestational hypertensive disorders [Bourjeily et al 2010;Calaora-Tournadre et al 2006;Franklin et al 2000;Perez-Chada et al 2007;Ursavas et al 2008] (OR 1.8-2.3 in most studies) [Bourjeily et al 2011] and gestational diabetes (aOR 2.1, 95% CI 1.3-3.4) [Bourjeily et al 2011;Facco et al 2010]. In addition, higher rates of unplanned Caesarean deliveries were found to be associated with both loud snoring [Bourjeily et al 2011] and OSA [Louis et al 2010].…”
Section: Discussionmentioning
confidence: 99%